Vận dụng mô hình học tập tự điều chỉnh của Zimmerman trong dạy học tích hợp giáo dục đạo đức lối sống cho học sinh tiểu học - Nguyễn, Diệp Ngọc; Nguyễn, Hương Giang (Tạp chí Giáo dục, 2025)
John Dewey (1938) affirmed: “Education is not preparation for life; education is life itself”. This emphasizes that moral and lifestyle education needs to be associated with practical experience. In the 2018 General Education Program, integrated teaching is identified as an effective method to develop students' qualities and abilities and link subjects. Within the framework of the article, we study Zimmerman's self-regulated learning model and apply it in integrated teaching to educate moral and lifestyle for primary school students. The research results show that this model both enhances self-regulation in learning and contributes to the formation of moral values and practical life skills, creating a foundation for the comprehensive development of primary school students.